ANALISIS KUALITAS LAYANAN E-HEALTH SURABAYA: PENDEKATAN INTEGRATIF E-SERVQUAL DAN IMPORTANCE PERFORMANCE ANALYSIS (IPA) - Muhammad Iqbal Hafish Setiawan; Riza Akhsani Setyo Prayoga; Aris Kusumawati (Program Studi Sistem Informasi, Universitas Banten Jaya, 2024)
I In an effort to improve health services, Surabaya City Health Service provides an innovation through the implementation of the E-Health system. E-Health is an information technology development that aims to provide a service system in the form of an online queue for patients at Surabaya health centers and hospitals. Based on the findings that have been made, there are several complaints about E-Health, which can impact the level of patient satisfaction with their experience using E-Health services. E-Health is part of an online-based service system, so the E-Servqual method is used. Additionally, the IPA approach used in this research identified the key attributes that need improvement to maximize user satisfaction and display priorities for improvement, allowing for a clearer view of which areas require immediate attention and action to improve the overall quality of E-Health services. The results of the research show that all dimensions still have measurable negative gap values, indicating specific areas where service quality does not meet user expectations. Specifically, the quality of service is rated at 0.86, which is less than 1, signifying that there are still aspects of the E-Health service that need enhancement. The attributes included in Quadrant I priority improvements on the Cartesian Importance Performance Analysis diagram are E4, E3, C4, P1, and RE4. Therefore, it is necessary to immediately address these main priorities so that E-Health services can be optimized and more satisfactory for users.